Swacha Bharat Abhiyan’s WaSH Technique” – Assessment of Knowledge and Practices in Urban Slum Settings: A Crosssectional Study - M.C. Yadavannavar; Praveen Ganganahalli; Soumya Mirji; Sneha Arkeri; Sadafara Janwekar (Indian Journal of Forensic Medicine & Toxicology, 2022)
Background: Safe drinking water, sanitation and healthy hygienic practices are essential for anindividual to carry a healthy life and absence of these is directly or indirectly responsible for mostcommunicable and non-communicable diseases. Objective: To assess the current status of knowledge&the level of practice regarding WaSH among urban slum dwellers. Methods: A cross-sectional studywas conducted in urban slums of field practice area of Shri B. M. Patil Medical College, Vijayapur.Using systematic random sampling method, the sample size of 384 households was selected. Data wascollected through house-to-house survey using predesigned questionnaire by interviewing one adultrespondent from each selected householdabout knowledgeand practices regarding water, sanitation andhygiene. Results: The average age of the adult respondent of the house was 40.65 ± 17.54 years amongwhich majority were females (63.80%). Only 28.39% of households had knowledge regarding waterborne diseases& around 72.4% of households were aware of Swacha Bharat Abhiyan. Conclusion:Even though Swacha Bharat Abhiyan was initiated in 2014 there is a clear gap between their knowledgeand their actual practice. Therefore, better measures have to be taken to spread awareness among thepublic.